Aktion Poliphile. 1989. (1998)
Propuesta de vivienda para un concurso en Wiesbaden, Alemania. Por <Ushida Findlay Partnership>.
Keywords: USHIDA, EISAKU; FINDLAY, KATHRYN; WIESBADEN; ALEMANIA; VIVIENDAS UNIFAMILIARES; CONCURSOS; PROYECTOS